Pendampingan Usaha Produk Tas Anyaman Berbasis Marketing Mix di Desa Sukorejo Kabupaten Ponorogo - Anisa Hilmi Fuadah; Teguh Ansori (Social Science Academic, 2025)
One of the MSMEs that have a pretty big opportunity is the craft of plastic woven bags. This community service was carried out in the plastic woven bag craft business unit owned by Mrs. Nikmah in Dukuh Krajan, Sukorejo Village, Sukorejo District, Ponorogo Regency. This service using the Asset-based community development (ABCD) method is considered to be the right approach to the above problem which is an approach to community development that is in a large flow. This service to the community provides assistance in terms of marketing and product promotion. Promotion and marketing assistance aims to introduce woven products to the wider community so that they can increase sales of woven bags. The purpose of this service activity is to help provide solutions to problems related to marketing aspects by introducing a marketing mix strategy. The results of this activity show that the assistance carried out is able to encourage these business actors to maintain their business by maximizing marketing and promotion aspects. In practice, The prospect of developing a plastic woven bag business in Dukuh Krajan, Sukorejo Village, Sukorejo District, Ponorogo, showed significant results, including the introduction of a marketing mix strategy that can support woven business productivity and expand marketing by utilizing social media and to make products more recognizable the broad public.